A Three-Dimensional Finger-Tapping Framework for Recognition of Patients With Mild Parkinson’s Disease - Junjie Li; Huaiyu Zhu; Haotian Wang; Bo Wang; Zhidong Cen; Dehao Yang; Peng Liu; Wei Luo; Yun Pan (IEEE, 2023)
The finger tapping test is a widely-used and important examination in the Movement Disorder Society Clinical Diagnosis for Parkinson’s Disease. However, finger tapping motion could be affected by age, medication, and other conditions. As a result, Parkinson’s disease patients with mild sign and healthy people could be rated as similar scores on the Movement Disorder Society-sponsored revision of the Unified Parkinson’s Disease Rating Scale, making it difficult for community doctors to perform diagnosis. We therefore propose a three-dimensional finger tapping framework to recognize mild PD patients. Specifically, we first derive the three-dimensional finger-tapping motion using a self-designed three-dimensional finger-tapping measurement system. We then propose a three-dimensional finger-tapping segmentation algorithm to segment three-dimensional finger tapping motion. We next extract three-dimensional pattern features of motor coordination, imbalance impairment, and entropy. We finally adopted the support vector machine as the classifier to recognize PD patients. We evaluated the proposed framework on 49 PD patients and 29 healthy controls and reached an accuracy of 94.9% for the right hand and 89.4% for the left hand. Moreover, the proposed framework reached an accuracy of 95.0% for the right hand and 97.8% for the left hand on 17 mild PD patients and 28 healthy controls who were both rated as 0 or 1 on the Movement Disorder Society-sponsored revision of the Unified Parkinson’s Disease Rating Scale. The results demonstrated that the proposed framework was less sensitive to traditional features and performed well in recognizing mild PD patients by involving three-dimensional patter features.